THE TRANSFORMATION OF MADRASAH THROUGH THE USE OF EDUCATION TECHNOLOGY - Siminto; H. Achmad Ruslan Afendi; Syukri Fathudin Achmad Widodo (International Journal of Teaching and Learning, 2024)
This study examines the implementation of educational technology in the process of transformation of the madrasah. The aim is to understand the impact of the use of technology in madrasah education, as well as to give recommendations to improve the effectiveness of its implementation. The research focuses on how technology can be used to enrich learning processes, improve administrative efficiency, and support distance learning. The method used in this research is the method of literature study, i.e. by collecting, analyzing, and concluding various literary sources related to research topics. These data sources include scientific articles, journals, books, research reports, and other relevant online documentation. The results of this study show that the use of technology in madrasah education has a significant impact on improving the quality of learning and wider access to learning resources. However, the research also found challenges in its implementation, including the uneven technological infrastructure and the need for technological training for teachers.